Maternal Mortality and Morbidity Associated with Primary PPH In Patients at Allied Hospital Faisalabad - Majeed, Saira; Tahira, Tasnim; Younis, Zirwa; Usman, Shehreen (Indus Journal of Bioscience Research, 2025)
Background: Postpartum hemorrhage (PPH) is a leading cause of maternal mortality, especially in developing countries like Pakistan. Uterine atony accounts for 80% of cases. Effective prevention and prompt treatment remain critical. Objectives: to evaluate the burden of PPH-related maternal complications and mortality in a tertiary care setting in Pakistan and to analyze risk factors, management strategies, and outcomes. Study Setting: The study was conducted in the Department of Obstetrics and Gynecology, Allied Hospital, Faisalabad. Duration of Study: The study was conducted over a specified period using a cross-sectional study design. Data Collection: A total of 220 patients with primary PPH were included, and data on demographic characteristics, PPH causes, interventions, maternal morbidity, and mortality were analyzed using SPSS version 25. Statistical tests were performed to identify significant associations (p ≤ 0.05). Results: The majority of participants were aged 18-35 years, with a mean BMI of 26.57 ± 4.80. Uterine atony was the leading cause of PPH (44.5%), followed by retained placenta (30.0%) and genital trauma (18.6%). Oxytocin was the most frequently used uterotonic agent (40.5%), while 10.0% of cases required surgical intervention. Maternal morbidities included anemia (17.7%), sepsis (8.6%), DIC (8.2%), and acute renal failure (6.4%), with a mortality rate of 7.73%. Conclusion: PPH remains a significant cause of maternal morbidity and mortality in Pakistan, with uterine atony as the predominant cause. The high prevalence of anemia underscores the need for improved maternal nutrition. Strengthening institutional delivery services, timely risk assessment, and expanding access to uterotonic agents are essential for reducing PPH-related complications.